COVID-19 Pandemic and Irritable Bowel Syndrome — is there a Relationship? - V. A. Akhmedov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2022)
The aim: to reflect the features of the course of irritable bowel syndrome during the COVID-19 pandemic.Key points. It has been noted that the COVID-19 may contribute to the formation of post-infectious functional gastrointestinal diseases, given that angiotensin-converting enzyme-2 (ACE-2) receptors, the site of binding of the SARS-CoV-2 virus to human cells, are also present in epithelial intestinal cells; virus was found in feces in about half of patients, gastrointestinal symptoms, including diarrhea occur in about one fifth of patients, fecal calprotectin, a marker of GI inflammation is elevated in patients with COVID-19, macroscopically as well as histologically, patients show signs of damage mucous membrane of the gastrointestinal tract, and also, as noted above, they have a dysbiosis of the intestinal microbiota.Conclusion. It was shown that during the pandemic, more than 90 % of the interviewed patients with IBS had an exacerbation of IBS with an increase in symptoms such as bloating and cramps, and 75 % of them said that the exacerbation of symptoms was reflected in the activity of patients in everyday life. These factors dictate the need for an integrated approach in the management of such a group of patients with the use of modern multi-target drugs that affect the pathogenetic factors in the formation of functional gastrointestinal diseases, one of which is the Kolofort drug due to the triple multi-target mechanism of action on the pathogenesis of functional gastrointestinal diseases.